Dynamic System Model for Optimizing Clean Water Distribution in Balikpapan City - Lasti Ningsih; Christopher Davito Prabandewa Hertadi; Bayu Nur Abdallah (G-Tech: Jurnal Teknologi Terapan, 2025)
Balikpapan City, as one of the supporting cities for the Nusantara Capital City (IKN) in East Kalimantan, faces significant challenges in meeting the demand for clean water. The increase in population due to migration and infrastructure development following the relocation of the IKN has led to a continuous rise in the demand for clean water. The rate of water loss, or Non-Revenue Water (NRW), is quite high, reaching 25.85%. This situation has resulted in low distribution efficiency and highlights a gap between the available clean water distribution system and the actual needs of the community. As a result, clean water service coverage reached only 80.07% in 2022. This study aims to identify the factors influencing clean water distribution, develop a dynamic system model, and formulate optimal scenarios. The research method used is a dynamic systems approach, which enables comprehensive analysis of the cause-and-effect relationships between variables in the clean water distribution system, as well as simulation of various policy scenarios to find the most effective and sustainable solutions. Simulation results show significant dynamics in clean water distribution. From 2023 to 2035, pipeline length increased from 1.4 million meters to 1.6 million meters, yet clean water consumption decreased to 23.67 million m³ in 2029 and 23.15 million m³ in 2035. Of the three designed scenarios, Scenario 3, which involves a 4.2% annual increase in pipeline repair rates and a 1.47% annual increase in the number of customers, proved to be the most effective. This scenario successfully reduces pipeline leakage rates and significantly improves distribution coverage.